Role of sonography done by clinicians/surgery residents in the diagnosis and management of clinically palpable breast lumps - Thapa, AS; Ghimire, R; Joshi, R; Dongol, UMS; Singh, DR (Journal of Society of Surgeons of Nepal, 2016)
Introduction and Objective: The aim of the study is to correlate the sonographic findings of breast ultrasound done by clinicians/surgery residents with radiologists and also to correlate the sonographic findings of breast ultrasound with cytopathological or histopathological findings. Materials and Methods: A prospective observational study conducted at KMCTH from March 2014 to March 2015. All consecutive patients presenting with clinically palpable breast lumps were included in the study. A sample size of 30 patients was taken. All patients with clinically palpable solid breast lumps were subjected to ultrasound by a clinician/surgical resident. Ethical clearance was taken from the institutional review board and informed consent was taken from the individual patients. Results: We found that the sonography done by clinicians/surgery residents had 100% sensitivity, 84.6% specificity and PPV of 50%. There was significant correlation between the findings of the surgery residents and radiologists and the cytopathology/histopathology as well. Conclusion: Breast Sonography performed by clinicians/surgery residents is comparable to radiologists in the diagnosis of clinically palpable breast lumps. It has good correlation with cytopathological and histopathological findings.